2020
DOI: 10.37624/ijert/13.8.2020.1917-1920
|View full text |Cite
|
Sign up to set email alerts
|

Date Fruits Grading and Sorting Classification Algoritham Using Colors and Shape Features

Abstract: The kingdom of Saudi Arabia produces almost 400 varieties, is the largest producer of dates in the worlds in dates fruit industries. The date's industries have facing problems in date grading and sorting during harvesting and agriculture products industries. Since human experts have some limitations such as tedious and timing delay consuming the processing delay as a result of date products costly. The computer vision algorithms are used to reduce the powers of mankind by automatically detect and classify an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Several imaging techniques have been proposed that rely on template matching to identify the pest [ 12 ]. An IoT-based smart palm-weevil monitoring system was developed based on using a web/mobile interface to detect the red palm weevil via sensors [ 1 ]. By applying 10 state-of- the-art data mining algorithms for classifications, tremendous work was done in 2021.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Several imaging techniques have been proposed that rely on template matching to identify the pest [ 12 ]. An IoT-based smart palm-weevil monitoring system was developed based on using a web/mobile interface to detect the red palm weevil via sensors [ 1 ]. By applying 10 state-of- the-art data mining algorithms for classifications, tremendous work was done in 2021.…”
Section: Related Workmentioning
confidence: 99%
“…The limits of the proposals are also adjusted with respect to linking boxes by regression. Second, for each region proposal, the features within the region are first aggregated into a feature map of constant size (i.e., RoI pooling [ 1 ]). Using the pooling feature, a DNN classifier then computes the probabilities of object classes and simultaneously regresses the detection limits for each object class.…”
Section: Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To deal with the problem of limited number of labeled images, authors in [28] suggested using an evolutionary algorithm along with an AdaBoost training procedure to check the quality of date fruit. In [29] , a hand-designed basic color and shape features were utilized to classify dates into three classes of quality namely class A, B and C. In another research [30], Mozafati dates were classified, based on length and freshness parameters, into different categories, from very poor to the excellent quality.…”
Section: Related Workmentioning
confidence: 99%